One-stage hybrid surgery for acute Stanford type A aortic dissection with David operation, aortic arch debranching, and endovascular graft: a case report - Liu, Lulu; Qin, Chaoyi; Hou, Jianglong; Zhu, Da; Zhang, Bengui; Hao, Ma; Yingqiang, Guo (Journal of Thoracic Disease; Vol 8, No 12 (December 31, 2016): Journal of Thoracic Disease, 2016)
Acute Stanford type A aortic dissection requires an extremely complex surgical strategy and presents high risk of complications. Although many different procedures were reported to treat this aortic dissection, high mortality rate and incidences of complications still exist. This study presents a 59-year-old lady with acute Stanford type A aortic dissection, which originated from the aortic root to proximal part of right external iliac artery and involved the brachiocephalic trunk, left carotid artery, celiac trunk, and left renal artery. The patient underwent one-stage hybrid surgery of David procedures, debranching, and endovascular aortic repair under ultrasound-guided aortic arch cannulation cardiopulmonary bypass (CPB). The surgery was successfully performed, and the patient showed no post-operative complication. The one-staged hybrid surgery of David procedures, debranching, and endovascular aortic repair provides novel and well-designed combined techniques for treating complex acute Stanford type A aortic dissection. Our techniques significantly lowered the risks, thereby expanding the indications of surgical intervention for acute Stanford type A aortic dissection.